ANALYSIS OF INHIBITING FACTORS, COMPARATIVE PATTERNS, AND METHODOLOGICAL GAPS OF LACK OF INTEREST IN ENGLISH PROGRAM: SYSTEMATIC LITERATURE REVIEW - Ridianto Ridianto; Riyadi Saputra; Multi Efrini; Roza Susanti; Desfi Yenti; Muhammad Yazid Fakhri (Universitas Mahaputra Muhammad Yamin, 2026)
This study aims to identify the dominant factors inhibiting prospective students' interest in an English Program, compare this pattern of low interest with other study programs, and uncover theoretical and methodological gaps in measuring the construct of